Analysis of Langkolome River Flood, Wambona Village, Muna Regency (Case Study: Langkolome River, Wambona Village, Muna Regency) - Hasrudin, La Ode; Lakawa, Irwan; Sudardjat, Catrin; Sufrianto, Sufrianto (Sultra Civil Engineering Journal (SCiEJ), 2023)
Rivers are natural channels on the surface of the earth to drain water, apart from that, of course, interactions between discharges, other factors such as human activities along rivers give different characteristics of river formation. the largest portion comes from land clearing activities around the Langkolome river body located in Wambona Village, South Wakorumba District, Muna Regency. Based on the results of the calculation of the flood discharge of the Langkolome River in Wambona Village from 10 years of rainfall data, namely Q10 = 128,773 m3/sec, Q25 = 244,067 m3/sec. The capacity of the Langkolome river which has an impact on flooding Q = 158,063 m3/s. The maximum rainfall is greater than the capacity of the river, so this causes flooding in the Langkolome River, Wambona Village, Muna Regency